Exploring The Potential of Visual Communication Design Education: Transforming Education Paradigm - Kharisma Creativani (Visual Heritage: Jurnal Kreasi Seni dan Budaya, 2023)
The field of visual communication design (VCD) has been growing in recent years, with advances in technology and the emergence of more sophisticated tools for creating visual media. Recently, the trend in visual communication study model is shifting towards more interdisciplinary approaches, combining traditional design elements with technology, psychology, and media studies. Despite the tremendous increase in the number of college, university, and art school design programs over the past two decades, it’s has been difficult to impose a formula that ensures a solid core curriculum, and a general handbook for how visual communication design should be taught and learned. This paper seeks to explore the potential of visual communication design education to transform existing educational paradigms. It will draw on current literature to discuss the emerging trends and applications of VCD education, exploring how this type of education can be used to create meaningful learning experiences that are relevant to the changing needs of today’s learners.